O discurso de jornalistas na atividade de trabalho em jornais locais e independentes no Brasil e na França: uma análise ergológica e semiolinguística - Blank, Julia Caroline Goulart (2023)
This study addresses the interface between language and work, more specifically the work activity of journalists who work in local and independent printed newspapers in Brazil and France. We set out as a general objective: to analyze the speeches of Brazilian and French journalists who work in local and independent media with a focus on the communication contract and its reflections and meanings in the work activity, knowledge and discursive strategies of these professionals during the performance of the act of language as staging. The view of ergology (Schwartz, 1998, 2009, 2011, 2014) is capable of providing a comprehensive overview so that we can identify how journalists act in work situations and how their role is (de)formed over time. Semiolinguistic Discourse Analysis, proposed by Charaudeau (2004, 2005, 2016; 2017; 2018; 2020), meets this reflection to provide support regarding language in action at work. This is an exploratory, bibliographic and field research, with a qualitative approach. The workers who took part in the research, as research subjects, are journalists who work in local and independent media outlets in Brazil and France. The research corpus consists of data collection, carried out through in-depth, semi-structured interviews, carried out after systematic observation of work in journalistic newsrooms. The analyzes developed allow us to support the thesis that the discourses, expressed in the different communication contracts, in which journalists engage, shape the work activity, influence the construction of labor knowledge constituted and invested in the activity and act in the way professionals they renormalize their activity, establishing discursive strategies in carrying out the act of language as mise-en-scène. The elocutionary modalities allowed us to access the implicit carried in the professionals' speech, revealing discursive strategies that indicate that journalists take their personal values ​​to the professional environment and the infidelity of the environment confronts them with dramatic uses of themselves by themselves and by others, which They often go against these values: it is the previous discourses, coming from previous norms, that imply the erosion and devaluation of the profession in society.